GARDU RONDA SEBAGAI KARYAARSITEKTUR VERNAKULAR KAJIAN TERHADAPBENTUK, STRUKTUR DAN FUNGSI - Sumarjo Sumarjo H. (Universitas Negeri Yogyakarta, 2006)
ABSTRACTThis research is aimed to identify the typology of form, structure and functionof the Watchman Station Patrol building as masterpiece of architecturevernacular. Sample of research amount of 10 buildings of watchman station,taken by snowball in region Sleman and its surroundings. To analyze thevariation of form growth, structure and function of the Watchman station Patrolbuilding, a fundamental approach model of typology and also continuity andchange is applied.Result of research indicates that geometry of space of the WatchmanStation Patrol building showing the remain uniform, that is the square geometry.Typology of structure of the Watchman Station Patrol building shows theconventional uniform; that is; system structure mark with lines with the wall atone blow as burden taker, open wall is mostly arranged in watchman station,especially at shares fagade. Watchman station also Shows a manifest Functionfor rendezvous as well as keep the warehouse places. Locus of watchmanstation determined by road axis of the orchard collector and center of the localcountryside governance. The latent function could be changed overtime dependon the society need; it supports the social and economic function of society.However, the core elements are remain, those are geometry of space, superstructure and setting of locus of the Watchman station Patrol building.Keywords: vernacular, form, structure, function